1999
DOI: 10.1161/01.res.84.12.1416
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Platelet-Derived Nitric Oxide and Enhanced Hemostasis in Mice Lacking the NOSIII Gene

Abstract: Abstract-Endothelial nitric oxide synthase (eNOS) has been identified in human platelets. Although platelet-derived nitric oxide (NO) has been shown to inhibit platelet recruitment in vitro, its role in the regulation of the hemostatic response in vivo has not been characterized. To define the role of platelet-derived NO in vivo, we studied mice that lacked a functional eNOS gene (NOSIII). Surface P-selectin expression in platelets from eNOS-deficient mice was not significantly altered; however, bleeding times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
175
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(185 citation statements)
references
References 35 publications
6
175
1
3
Order By: Relevance
“…a significant antithrombotic effect, 15,16 studies suggesting that the absence of platelet eNOS has little consequence on arterial thrombus formation, 32,33 and even studies showing an impaired ability of eNOS −/− mice to form occlusive thrombi. 34 Differences in experimental conditions and animal models may probably explain the conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a significant antithrombotic effect, 15,16 studies suggesting that the absence of platelet eNOS has little consequence on arterial thrombus formation, 32,33 and even studies showing an impaired ability of eNOS −/− mice to form occlusive thrombi. 34 Differences in experimental conditions and animal models may probably explain the conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Besides endothelium, eNOS is present in other cells, including platelets, [12][13][14] and several in vitro and in vivo observations in animals and in humans suggest that platelet-derived NO plays a significant anti-inflammatory and antithrombotic role. [15][16][17][18][19] dl-Nebivolol was previously reported to inhibit ADP-and collagen-induced aggregation of human platelets in vitro, 20 an effect prevented by the previous exposure of platelets to a NOS inhibitor, such as L-NG-nitroarginine methyl ester, and enhanced by preincubation with l-arginine, the substrate of NOS, suggesting that the antiplatelet effect of dl-nebivolol is mediated by an enhanced release of NO from platelets. 4 © 2014 American Heart Association, Inc. Objective-dl-Nebivolol, a selective β1-adrenergic receptor antagonist, besides its hypotensive activity exerts vasodilatory and platelet inhibitory effects in vitro by a mechanism involving nitric oxide (NO).…”
mentioning
confidence: 99%
“…NO regulates thrombosis in part by inhibition of platelet adhesion and aggregation (2,5,6). One well described pathway by which NO regulates platelet activation is mediated by guanylate cyclase (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…For example, Freedman et al (6) demonstrated that bleeding times were decreased in eNOS null mice. An interesting aspect of their study is that the investigators also found that bleeding times in wild-type mice transfused with platelets lacking eNOS were markedly decreased compared with mice transfused with wild-type platelets.…”
mentioning
confidence: 99%
“…Data from experimental studies showed controversial findings concerning the existence of platelet NOS. Both constitutive and inducible NO synthases have been identified in human platelets [5], and data from an experimental study performed on eNOS deficient mice demonstrated that stimulated platelets were found to lack stimulation-dependent NO release [6]. Nevertheless, recently it has been demonstrated that human and mouse platelets do not express eNOS/iNOS [7].…”
Section: Introductionmentioning
confidence: 99%